Mitigating Emerging Environmental Issues in the Contemporary World: the Role of Faith-based organisations and Implications for their Growth in Nigeria - J. I. Offor; J. E. Umunnakwe (Budapest International Research and Critics University, 2021)
The world today is confronted with many different emerging environmental issues. The recognition of an issue as ‘emerging’ is based on newness. Newness of an issue can be as a result of new scientific knowledge, new scales or accelerated rates of impact, a heightened level of awareness, and, or new ways to respond to the issue. This paper highlighted major emerging environmental challenges, to include: climate change, ozone layer depletion, energy crisis, biodiversity loss, flooding, overpopulation, and pollution. Scientific/policy solutions to environmental issues were discussed. The paper revealed the difficulty of finding universal solutions to environmental problems. A new strategy is needed to inflict urgency of environmental protection that can relate to any person’s principles no matter their walk of life. For this reason, it was necessary to evaluate the legitimacy of the church, a veritable faith-based organisation as a possible motivation and tool to mitigate environmental challenges. Christianity with their large numbers in Nigeria was seen as having the potency to make people obey environmental laws; educate people on the need to be environmentally friendly in all their activities- the ‘green church’ was recommended in the paper. It was asserted that the green church will attract more worshippers, therefore leading to church growth in the 21st century.